Impact of pre-existing dengue immunity on human antibody and memory B cell responses to Zika - Paulina Andrade (Nature Portfolio, 2019)
Here, Andrade et al. assess the memory B cell (MBC) and antibody response to Zika virus (ZIKV) in individuals with and without prior dengue virus (DENV) infection and find that ZIKV infection elicits a robust and specific MBC response that is only modestly affected by the number of prior DENV infections.